Sapindus rarak as Saponin Source and the Effect to Meat, Blood, and Fecal Cholesterol in Broiler Chicken - Baidlowi, Ahmad (Indonesian Society of Animal Science in collaboration with Indonesian Ministry of Agriculture and Faculty of Animal Science UGM, 2014)
This Research was conducted to determine the effect of Lerak fruit (Sapindus rarak) extraction as feed additives on meat, blood, and fecal cholesterol of broiler were fed with basal diet. sixty male broiler chickens strain Lohmann 7 days old were divided into four groups of treatment with Lerak fruit estract as saponin source with different levels 0, 0.1, 0.3, and 0.5%. Each treatment consisted of three replication, and each replication using five chickens. Data with collected were meat, blood, and fecal cholesterol. Data were analyzed, using one way ANOVA design, the significancy of different were tested by Least Significant Different (LSD) test. The result from this research showed that the treatments using saponin from Lerak Fruit extraction with different level (0; 0.1, 0.3; 0.5%) decreased significantly (P<0.05) meat cholesterol and blood triglyceride levels, consecutively: (118.21; 98.45; 98.34; 91.03 mg/100 ml) and (66.67; 51.85; 29.63; 33.33 mg/100 ml). The treatments also decreased significantly (P<0.05) blood cholesterol, blood HDL level and cholesterol in excreta, consecutively: (105.26; 126.32; 147.37; 143.86 mg/100 ml), (31.67; 38.87; 39.60; 44.00 mg/100 ml) and (179.11; 212.77; 265.93; 207.59 mg/100 ml), and also significantly affected (P<0.01) to blood LDL level (81.06; 94.47; 107.77; 104.26 mg/100 ml). It could be concluded that the addition of saponin from Lerak fruit extraction up yo 0.5% can affect to cholesterol level and metabolism in broiler chicken.